Microstructure of spark plasma sintered TiC-TiB2-SiCw composite - Yu, Hao; Namini, Abbas Sabahi; Delbari, Seyed Ali; Le, Quyet Van; Kim, Dokyoon; Cha, Joo Hwan; Lee, Sea-Hoon; Kim, Soo Young; Jang, Ho Won; Shokouhimehr, Mohammadreza (Elsevier BV, 2022)
This research intends to implement a complementary study on the consolidation and microstructure of TiC-based ceramics incorporating 30 vol% TiB2 and 10 vol% SiC whiskers (SiCw). The spark plasma sintering was employed as the manufacturing tool to produce the designed composite under the sintering pressure of 40 MPa for 7 min at 1900 degrees C. The X-ray diffraction study and the microstructural observations revealed the formation of graphite as an in-situ phase during the sintering process, as a result of carbon deposition from the crystalline structure of the TiC matrix. Although the SiC introduced to the composite was needle-shaped, no SiC whiskers could be found in the final microstructure due to the nucleation and growth of new SiC grains. Additionally, it was suggested that the surface oxide impurities available on the starting powders could contribute to some reactions, resulting in the in-situ formation of SiC, TiB2, and TiC ingredients. Furthermore, the grain growth phenomenon led to the formation of intragranular TiB2 grains in the TiC matrix. The plastic deformation and the applied external pressure with an inconsistency among the thermal expansion coefficients of TiB2, TiC, and SiC over the cooling stage resulted in the generation of crystalline defects, e.g., dislocations and distorted atomic planes.